Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T08:11:20+01:00
Założenie x²+bx+b²-1 =0
Δ≥0 => b²-4b²+4≥0 => -3b²+4≥0 => b²-4/3≥0 => (b-2√3/3)(b+2√3/3)≥0 => b∈(-∞;-2√3/3)+(2√3/3;+∞)
2√3/3≈1,15

x₁⁴+x₂⁴=1
(x₁⁴+2x₁²x₂²+x₂⁴)-2x₁²x₂²=1
(x₁²+x₂²)²-2x₁²x₂²=1
(x₁²+2x₁x₂+x₂²-2x₁x₂)²-2x₁²x₂²=1
((x₁+x²)²-2x₁x₂)²-2x₁²x₂²=1

Wzory Viete'a
x₁+x₂=-b/a u nas =>x₁+x₂=-b
x₁*x₂=c/a u nas => x₁*x₂=b²-1
Podstawiając do ((x₁+x₂)²-2x₁x₂)²-2x₁²x₂²=1
((-b)²-2(b²-1))²-2(b²-1)-1=0
(b²-2b²+2)²-2b²+2-1=0
(2-b²)²-2b²+1=0
4-4b²+b⁴-2b²+1=0
b⁴-6b²+5=0 b²=t, t≥0
t²-6t+5=0
Δt=36-20=16
√Δt=4
t₁=(6-4)/2=1
t₂=(6+4)/2=5
(b-1)²=0 => b=1 lub b=-1 ∉ do założeń
(b-5)²=0 => b=5 lub b=-5

Odp. b∈{-5;5}

Liczę na naj.